Whitefly genomes contain ribotoxin coding genes acquired from plants - Lapadula, Walter Jesús (2020)
Ribosome inactivating proteins (RIPs) are RNA N-glycosidases that depurinate a specific adenine residue in the conserved sarcin/ricin loop of 28S rRNA. These enzymes are widely distributed among plants and bacteria. Previously, we have described for the first time RIP genes in mosquitoes belonging to the Culicidae family. We showed that these genes are derived from a single event of horizontal gene transfer (HGT) from a prokaryotic donor. Mosquito RIP genes are evolving under purifying selection, strongly suggesting that these toxins have acquired a functional role. In this work, we show the existence of two RIP encoding genes in the genome of the whitefly Bemisia tabaci, a hemiptera species belonging to the Aleyrodidae family distantly related to mosquitoes. Contamination artifacts were ruled out analyzing three independent B. tabaci genome databases. In contrast to mosquito RIPs, whitefly genes harbor introns and according to transcriptomic evidence are transcribed and spliced. Phylogeny and the taxonomic distribution strongly support that whitefly RIP genes are derived from an independent HGT event from a plant source. These results, along with our previous description of RIPs in Diptera, suggest that the acquired genes are functional in these insects and confer some fitness advantage.